Projectification and its effects: The tyranny of time, the reconciliation of antinomies. - Coelho, J. V. (N/A, 2024)
A project defines a prospective figure, reflecting an Enlightenment concern, emerging since the 18th century: the concern with the oppressive influence of the tyranny of time, with a prospective time, the prediction of a desired future state. What presents the project as a dominant trait of modernity is, indeed, its focus on becoming and in what is yet to happen, and the (Promethean) desire to appropriate it. Thus, the project represents a quality of advancement towards the future, a possibility of liberating transcendence. In this sense, the project can represent for individuals, in symbolic and discursive terms, a place of proactivity, of provisional destinations, that can be accumulated, inhabited, enunciated. The increasing projectification of society, also observable in Portugal, by reflecting a socio-cultural orientation that fosters the particularization (of interests, identities, experiences) and the individualization (of lifestyles and life trajectories), thus delineates a particularly fertile field of interdisciplinary research.